The effect of renewable energy consumption on economic growth: Evidence from the renewable energy country attractive index. (15th September 2020) - Shahbaz, Muhammad; Raghutla, Chandrashekar; Chittedi, Krishna Reddy; Jiao, Zhilun; Vo, Xuan Vinh
Abstract: The use of non-renewable resources emits a high quantity of CO2 into environment, leading to a greenhouse effect, to reduce CO2 emissions all countries have shifted to use renewable energy sources. Therefore, this study re-examines the effect of renewable energy consumption on economic growth across 38 renewable-energy-consuming countries from 1990 to 2018. The dynamic ordinary least squares (DOLS), fully modified ordinary least squares (FMOLS) and heterogeneous non-causality approaches are applied. The empirical analysis confirms the presence of a long-run relationship between renewable energy consumption and economic growth. Further, we noted that renewable energy, non-renewable energy, capital and labor have positive impact on economic growth, particularly, renewable energy consumption has a positive impact on economic growth for 58% of the sample countries. The empirical results suggest that international cooperation agencies, energy organizers, governments, and associated bodies must act together in increasing renewable energy investment for low carbon growth in most of these economies. Highlights: This study evaluates the impact of sustainable and non-sustainable energy sources. It employs DOLS and heterogeneous non-causality approaches. The study estimated a time-series analysis of long-run output elasticities. Renewable energy has a positive and significant impact on economic growth. Cooperation agencies must act together in increasing renewable energy investment.